Benefits and Concerns regarding Use of Cannabis for Therapeutic Purposes Among People Living with Chronic Pain: A Qualitative Research Study. Issue 11 (2nd June 2022) - AminiLari, Mahmood; Kithulegoda, Natasha; Strachan, Patricia; MacKillop, James; Wang, Li; Pallapothu, Sushmitha; Neumark, Samuel; Sharma, Sangita; Sethi, Jagmeet; Zacharias, Ramesh; Blain, Allison; Patterson, Lisa; et al.
Abstract: Objective: Although there is growing interest in medically authorized cannabis for chronic pain, little is known about patients' perspectives. We explored perceptions of people living with chronic pain regarding benefits and concerns surrounding their use of cannabis for therapeutic purposes. Setting: A hospital-based clinic in Hamilton and two community-based interdisciplinary pain clinics in Burlington, Ontario, Canada. Methods: In this qualitative descriptive study, we conducted semi-structured interviews with 13 people living with chronic pain who used cannabis therapeutically, living in Ontario, Canada. We used thematic analysis, with data collection, coding, and analysis occurring concurrently. Results: People living with chronic pain reported important benefits associated with use of cannabis for therapeutic purposes, including reduced pain, improved functionality, and less risk of harms compared to prescription opioids. Most patients also acknowledged harms, such as grogginess and coughing, and there was considerable variability in patient experiences. Financial costs and stigma were identified as important barriers to use of cannabis. Conclusion: Evidence-based guidance that incorporates patients' values and preferences may be helpful to inform the role of cannabis in the management of chronic pain.